Factors of growth for the biggest Hungarian firms - Péter Juhász (Journal of Contemporary Economic and Business Issues, 2017)
Since the beginning of the financial crisis, one of the key challenges of the economic policy has been to boost the growth of firms, particularly in the CEE region. Various research has showed that obstacles limiting and boosters enhancing companies' development potential differ across companies. This paper builds on both publicly available financial reports and a detailed questionnaire targeting the top 200 Hungarian firms with the highest sales in 2015. In top management's opinion, the level of technology, innovation and export position improved most in the years 2013 to 2015. At the same time, results show that beside market factors and challenges within companies' discouraging regulations, the limited amount of available trained workforce, high tax burden, and management capabilities are the major obstacles of growth. Even the biggest firms do not form a homogeneous group: constraints are different when controlled for export intensity, ownership, location, and strategic focus. So, access to financing is a real issue only with locally owned firms.
Keywords: G32; L21; L25; H32; M21; 330; workforce; regulation; competiveness; export; ownership